Varying amylose and total starch content in potato tubers derived from Finland and Sweden - Bhat, Ramanath (SLU/Dept. of Food Science, 2015)
Plant growth is affected by a lot of resources, namely, water supply, sunlight, nutrients in the soil etc. This study investigates changes in potato starch composition derived from tubers grown in Finland and Sweden. In this project you will see the comparison between nine different varieties of potatoes (Asterix, Bintje, Desiree, Kuras, Maria, Maris Piper, Quadras, Rosmunda and Saturna) that were grown in Finland and those grown in Sweden. The hypothesis that growing conditions have an effect on amylose content and total starch content of the same variety was put to test among the sets of tubers. Starch powder was extracted using free-drying method from each set received from each source (Sweden and Finland) and compared. Analysis of amylose content and total starch content was done using Megazyme kits on extracted starch powder. The average calculated for amylose contents between sets of Kuras and Maria varied the most and averages calculated for total starch content varied the most between sets of Desiree and Kuras. The results indicate that growing conditions do have an effect on tubers, in specific, Desiree, Kuras and Maria.